METHODOLOGY FOR IMPROVING THE RELIABILITY OF 10–35 KV CABLE NETWORKS BASED ON AN INTEGRATED APPROACH - Tkachenko, Andrii (General Energy Institute of the National Academy of Sciences of Ukraine, 2026)
Modern challenges in the field of power supply to urbanized areas and industrial clusters demonstrate that medium-voltage cable networks (10–35 kV), which form the backbone of critical infrastructure, are highly vulnerable to emergency outages, leading to a significant increase in the integral reliability indices SAIDI and SAIFI. The purpose of this study is to develop and substantiate reservation algorithms aimed at improving the reliability of consumer power supply in such networks, taking into account economic feasibility and the prospects for implementing Smart Grid technologies in Ukraine. The research employs a comprehensive approach that combines graph theory for formalizing the topology of cable networks, mathematical optimization methods (linear programming, Koon-Mann models, Markov processes), as well as the use of modern simulation tools (DIgSILENT PowerFactory, MATLAB / Simulink, ETAP) to evaluate the effectiveness of reservation schemes. Particular attention is paid to consumer automatic transfer algorithms – from classical ATS to intelligent FLISR systems integrated into the Smart Grid environment. Modeling results and the analysis of practical case studies from Ukraine, Germany, and Poland confirm that the implementation of reservation schemes can reduce SAIDI values by 5–20 times and SAIFI by 2–4 times, depending on the network topology, which significantly reduces industrial losses and improves socio-economic security. The study also proves the economic feasibility of reservation based on the LCCA methodology, which balances capital expenditures for the construction of reserve lines with operational costs associated with outages. The conclusions justify that the greatest effect for Ukraine is achieved through the integration of key reservation schemes with automatic switching, the application of FLISR within Smart Grids, and the use of optimization algorithms that consider investment constraints. The practical result of the study lies in defining pathways for adapting international approaches to national conditions, thereby creating the basis for strengthening the resilience of Ukrainian power networks, integrating renewable energy sources, and forming a competitive energy system.